Immunohistochemical Characterization of Three Monoclonal Antibodies Raised against the Epidermal Growth Factor and Its Receptor in Non-Small-Cell Lung Cancer: Their Potential Use in the Selection of Patients for Immunotherapy. (11th December 2012) - Rengifo, Charles E.; Blanco, Rancés; Blanco, Damián; Cedeño, Mercedes; Frómeta, Milagros; Calzado, Enrique Rengifo
Abstract : Adequate methods to identify which lung cancer patients are most likely to benefit from the targeted drugs against both epidermal growth factor receptor/epidermal growth factor (EGFR/EGF) are needed. For this reason, we evaluated both the tissue reactivity of ior egf/r3 monoclonal antibody (Mab) in human lung carcinomas and its biological activity in NCI-H125 cells. Additionally, we assessed the tissue expression of EGF using two Mabs, CB-EGF1 and CB-EGF2. The overexpression of EGFR was detected in 33.33% and 62.71% of small-cell lung carcinoma (SCLC) and non-small-cell lung carcinoma (NSCLC), respectively. The ability of ior egf/r3 Mab to bind the extracellular domain of EGFR inhibiting cell proliferation and inducing apoptosis in NCI-H125 cells was also demonstrated. The EGF expression was observed in about 17% and 70% of SCLC and NSCLC, respectively. However, differences in the reactivity of CB-EGF1 and CB-EGF2 were evidenced. A dual expression of EGFR and EGF was observed in 16.67% and 57.63% of SCLC and NSCLC patients, respectively. But, a correlation between them was only obtained in NSCLC. Our results permit to recommend the development of diagnostic kits using ior egf/r3 and/or CB-EGF1 Mabs in order to achieve a better selection of patients to EGFR/EGF-targeting treatment.